Redescription of Tharyx killariensis (Southern) from Ireland and description of two new species of Tharyx from the Kattegat, Sweden (Polychaeta, Cirratulidae) - Blake, James A.; Göransson, Peter (Zootaxa, 2015)
Two new species of the cirratulid genus Tharyx are reported from shallow waters in the Kattegat inshore Sweden. In addition, the lectotype of Tharyx killariensis (Southern, 1914) is redescribed resulting in a revised concept of the noto- and neuropodial acicular spines of posterior parapodia for that species. These spines were originally reported as bidentate crotchets with sharply pointed teeth; in reality the spines have blunt, knob-shaped tips, typical of several other species of Tharyx. Both of the new species are atypical for the genus Tharyx. T. maryae n. sp. has an expanded posterior end more typical of the genus Aphelochaeta, but otherwise shares characters of Tharyx. T. robustus n. sp. has a body shape that is consistently broad and dorsoventrally flattened throughout, rather than elongate and narrow as in other species of the genus. Both of the new species, however, have short, blunt-tipped spines in far posterior parapodia. With the addition of the two new species, the genus Tharyx now includes 11 species that are compared and contrasted. Morphology that defines and characterizes species of Tharyx is reviewed.